Social and Economic Development of Rural Border Area in Malaka and Belu Regencies (Border of Indonesia-Timor Leste) - Hidayah, Ulul; Amo, Farisa Maulinam; Klau, Anggelina Delviana (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
Indonesia and Timor Leste have the same land area; these countries are located on Timor Island. It encourages interaction between regions, which can have positive or negative impacts. The adverse effects of the two countries' interaction must be minimized by formulating a strategy for developing border areas, especially village areas that directly border neighboring countries. This research aims to identify rural border communities' social and economic interactions and formulate development strategies for rural border areas in the Malaka and Belu Regencies. This research uses a qualitative research approach. The data collected includes a description of the social and cultural interactions carried out by rural communities and factual conditions that constitute strengths, weaknesses, threats, and opportunities in developing rural border areas. The analysis results explain that the interactions between rural borders include socio-cultural and economic interactions in trade activities. The strategy for developing rural border areas is to increase defense and security and maintain social cohesion in border areas; strengthen local potential in each village; encourage rural economic activities (BUMDes or Cooperatives) to grow and develop, and export rustic products; form clusters in rural border areas with the same potential; strengthening cooperation networks with higher education, the private sector and non-governmental institutions in improving and developing rural border areas; strengthening rural economic activities with rural border markets; increasing rural community participation in border area maintenance efforts; as well as improving access to basic infrastructure, in particular electricity, roads, water and telecommunications.